Delayed Neurological Deficit after Traumatic Odontoid Fracture - Yesaya Yunus; Julius July (Neurologico Spinale Medico Chirurgico, 2018)
Fractures of the odontoid process can lead to gross instability of the atlantoaxial complex and present a significant risk for a potentially catastrophic spinal cord injury. Type II odontoid fractures are the most common odontoid fractures and are unstable that may displace anteriorly or posteriorly. If left untreated, the patient may develop atlantoaxial dislocation that causes neurological deficit also progressive myelopathy. We described the surgical management of four patients with a delayed neurological deficit after odontoid fracture with a history of trauma and after triggered by traditional massage. Traction several days before operation applied to achieve reduction of atlantoaxial dislocation. Posterior instrumentation and correction of atlantoaxial dislocation were performed with interarticular screw fixation (Harm technique) in all of the patients. All of the four patients showed a reduction of the atlantoaxial dislocation and also a neurological improvement. Cervical traction followed by posterior instrumented correction may be an effective alternative to treating delayed neurological deficits after traumatic odontoid fracture.